OBSERVING A TEACHER PROFESSIONAL DEVELOPMENT PROGRAM AND TEACHER CAPACITY IN TEACHING PISA-LIKE READING - Karima Putri Rahmadina, - (2022)
This thesis presents one part of a collaborative research project of three state universities in West Java, Indonesia, aiming to develop the first stage of a training program for teachers to teach PISA-like reading conducted online in 2021. This thesis specifically reports on an aspect of the training program that is to do with the first stage of training English teachers to teach PISA-like reading as informed by the theory of characteristics of professional development program (Darling-Hammond et al., 2017; Garet et al., 2001), a model of measuring professional development impact (Desimone, 2009; Ingvarson et al., 2003, 2005), and SFL's text-based instruction (Emilia, 2011; Macken-Horarik, 2002; Rose & Martin, 2012). The study was done by exploring activities provided in the training program as well as the process of teacher change resulted from the training. The data were collected from observation of the training program, including observation of peer teaching sessions of three selected English teachers, interviews with the teachers and document analysis (questionnaires distributed by the training and lesson plans). The data were then analyzed using thematic analysis based on the framework of exploring impact of professional development program adapted from Darling-Hammond et al., (2017), Desimone (2009), Ingvarson et al., (2003, 2005). The result of the study shows that the training program supported the teachers to teach PISA-like reading by providing activities in the training program which attended to the characteristics of effective professional development program, which led to an improved knowledge, practice and efficacy in the teachers. This first stage of the training program can also be considered as a breakthrough as PISA reading in EFL context has not yet been implemented by OECD. Nonetheless, aspects of collaboration between teachers as well as follow-up measure from the training program on students' learning outcomes could still be improved. Hence, it is recommended for future study on TPD in teaching PISA-like reading to attend to these aspects to accomplish an even better result.